2009
DOI: 10.1111/j.1439-0272.1978.tb01327.x
|View full text |Cite
|
Sign up to set email alerts
|

Fertility of the Streptozotocin-Diabetic Male Rat

Abstract: Zusammenfassung Die Fertilität der Streptozotoxin‐Diabetes männlichen Ratte Bei juvenilen (30 Tage alt) und erwachsenen (über 120 Tage alt) männlichen Ratten wurde mit Streptozotoxin ein Diabetes induziert. Dieser Diabetes verursachte eine Reduzierung der Fertilitätsrate in 82% bei den juvenilen und in 57% bei den erwachsenen Tieren. Der Rückgang der Fertilitätsrate war begleitet von einem Abfall des Blut‐Tes‐tosterons und einer Atrophie der ventralen Prostata, der Koagulationsdrüsen und der Samenblasen. Histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
15
0
1

Year Published

2009
2009
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 23 publications
5
15
0
1
Order By: Relevance
“…The severity of diabetes and its complications were reflected in the testis metabolome, where, though all diabetic mice exhibited abnormal metabolic profiles, the severity of the abnormality was likely to be exacerbated by low body weight and overall physical well being. As has previously been shown, STZ treatment did not result in sufficient beta-cell destruction for diabetes to develop in all mice (Frenkel et al, 1978). Although there is weak GLUT2 expression in the mouse testis (Kokk et al, 2004), STZ does not appear to influence the testis directly.…”
Section: Metabolomics Of the Stz Diabetic Mouse Testismentioning
confidence: 67%
“…The severity of diabetes and its complications were reflected in the testis metabolome, where, though all diabetic mice exhibited abnormal metabolic profiles, the severity of the abnormality was likely to be exacerbated by low body weight and overall physical well being. As has previously been shown, STZ treatment did not result in sufficient beta-cell destruction for diabetes to develop in all mice (Frenkel et al, 1978). Although there is weak GLUT2 expression in the mouse testis (Kokk et al, 2004), STZ does not appear to influence the testis directly.…”
Section: Metabolomics Of the Stz Diabetic Mouse Testismentioning
confidence: 67%
“…From early in its use as an experimental model of DM, studies have reported on the decreased fertility of the STZ treated male rodent (Frenkel et al. , 1978; Paz et al.…”
Section: Discussionmentioning
confidence: 99%
“…Streptozotocin treatment does not always result in sufficient beta‐cell destruction for diabetes to develop (Frenkel et al. , 1978).…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in epithelial-stromal interaction certainly predisposes this gland in diabetic mice to be a prostate disease target. seminal fluid (Frenkel et al 1978;Mcculloch et al 1984). Cagnon et al (2000) and Ribeiro et al (2006) verified atrophied secretory cells, stromal hypertrophy, inflammatory processes, prostatic intraepithelial neoplasia and dilated secretory organelles in the ventral lobe of the prostate in non-obese diabetic mice.…”
Section: Discussionmentioning
confidence: 95%
“…Different experimental studies in the male reproductive system, which exhibited type 1 diabetes mellitus because of either chemical induction or spontaneous development presented retrograde ejaculation (Ellemberg 1980), urinary bladder dysfunction (Buck et al. 1976; Stefan 1996), sexual impotence and decreased spermatozoid number in the seminal fluid (Frenkel et al. 1978; Mcculloch et al.…”
mentioning
confidence: 99%